ANTIMICROBIAL EFFICACY OF PAPAYA SEED ETHANOLIC EXTRACT AGAINST SALMONELLA TYPHI THAT CAUSES TYPHOID FEVER - Alexander Simanjuntak; Adrian Adrian; Linda Chiuman; Claudia Tanamal (Universitas Negeri Gorontalo, 2022)
Salmonella typhi is a bacteria that causes typhoid . In Indonesia, the disease is an endemic throughout the year. Papaya that is often found to have efficacy as an antibacterial agent. The research is aimed to detect the antibacterial ability of ethanol extract papaya seeds to Salmonella typhi . Extraction method was done by soaking using 70 % ethyl alcohol solvent then agar diffusion method was used to find out Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) in antibacterial testing. The statistics will be examined through analysis of variance (one way ANOVA with p-value (Î±) set at 0.05). Liquid dilution method is utilized to assess Minimum inhibitory concentration while drop plate method is made to determine Minimum bactericidal concentration. The research discovered that ethanol extract of papaya seeds contain secondary metabolite compounds such as : phenolics, flavonoids, alkaloids, saponins, tannins and terpenoids at 100 % concentration was effective to inhibit Salmonella typhi growth with an area of 6,86 mm inhibition zone which is categorized as moderate. In this study, Ciprofloxacin was used for positive control and distilled water for negative control. The percentage of sample concentrations used are: 3%, 6%, 12%, 25%, 50% and also 100%. The research used Ciprofloxacin The ethanol extract of papaya seeds was not found to be an effective bactericidal agent against Salmonella typhi.